Proyecto de factibilidad para la producción y comercialización de galletas de arroz en el cantón Macará de la provincia de Loja - Gonzaga Salinas, Brayan David (2022)
The main objective of this thesis project is to determine the feasibility for the creation of a company for the production and commercialization of rice crackers in Macará canton of the province of Loja, and also that this project also serves as a guide to demonstrate the possibilities of business development in the generation of a new business project. In order to achieve the objectives, the following studies were carried out to determine the feasibility of the project. The feasibility project has a simple descriptive research of which bibliographic compilation techniques and surveys were designed through the determination of a sample of 353 surveys directed to families in the urban area of the city of Macará. In the market study it was determined taking into consideration referring to the same product an unsatisfied demand of 389,957 packages of cookies in the year 1 of 2023 by the families of the urban area of the Macará Canton, in addition a commercial plan was elaborated to introduce the new product through intermediaries such as neighborhood stores and supermarkets to compete in the market. The technical study determined an annual production capacity of 57,162 packages of rice crackers occupying a market share of 14.66% in year 1 of 2023, this annual capacity will remain the same during the five-year life of the project, also took into account the legal constitution of the company with their respective manuals of functions necessary for the operation of the company. The financial study determined a total investment of US$8,269.17. This investment is financed by the owner of the company, which accounts for 39.53%, and 68.61% through a bank loan from BanEcuador. Through the cost analysis it was determined that the selling price of the product to intermediaries is $0.95 cents per package of 6 units to finally be sold to the public at a price of $1.00 per unit during the five-year life of the project. The financial evaluation study determined the following indicators: Net Present Value of $14 753.27; Internal Rate of Return of 81.30 % which is higher than the opportunity cost; Benefit Cost Ratio delivers a result that for every dollar invested 0.16 cents of dollar of profit is obtained; the Capital Recovery Period shows that the investment is recovered in 1 year 4 months and 18 days; the sensitivity analysis with the increase in costs can support 6.95 % and with the decrease in income 5.97 % so the project is not sensitive up to these percentages to generate profitability. Finally, it is concluded that the present feasibility project is feasible with the results of the studies carried out, so it is advisable its execution since it demonstrates to deliver economic benefits from the moment it starts its operational phase.